Atrial fibrillation and atrial cardiomyopathies. (16th July 2021) - Baman, Jayson R.; Cox, James L.; McCarthy, Patrick M.; Kim, Daniel; Patel, Ravi B.; Passman, Rod S.; Wilcox, Jane E.
Abstract: Atrial fibrillation (AF) is the most common arrhythmia among adults. While there have been incredible advances in the management of AF and its clinical sequelae, investigation of atrial cardiomyopathies (ACMs) is becoming increasingly more prominent. ACM refers to the electromechanical changes—appreciated subclinically and/or clinically—that underlie atrial dysfunction and create an environment ripe for the development of clinically apparent AF. There are several subtypes of ACM, distinguished by histologic features. Recent progress in cardiovascular imaging, including echocardiography with speckle‐tracking (e.g., strain analysis), cardiovascular magnetic resonance imaging (CMR), and atrial 4‐D flow CMR, has enabled increased recognition of ACM. Identification of ACM and its features carry clinical implications, including elevating a patient's risk for development of AF, as well as associations with outcomes related to catheter‐based and surgical AF ablation. In this review, we explore the definition and classifications of ACM, its complex relationship with clinical AF, imaging modalities, and clinical implications. We propose next steps for a more unified approach to ACM recognition that can direct further research into this complex field.